2020
DOI: 10.3390/diagnostics10100780
|View full text |Cite
|
Sign up to set email alerts
|

The Elevated Pre-Treatment C-Reactive Protein Predicts Poor Prognosis in Patients with Locally Advanced Rectal Cancer Treated with Neo-Adjuvant Radiochemotherapy

Abstract: The aim of the present study was to investigate the association of the pre-treatment C-reactive protein (CRP) plasma level with survival outcomes in a cohort of 423 consecutive patients with locally advanced rectal cancer treated with neo-adjuvant radiochemotherapy followed by surgical resection. To evaluate the prognostic value of the CRP level for clinical endpoints recurrence-free survival (RFS), local-regional control (LC), metastases-free survival (MFS), and overall survival (OS), uni- and multivariate Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
1
6
1
Order By: Relevance
“…A study conducted by Partl R et al, in 2020 concluded that the increased pretherapy CRP has a poor outcome in patients. 12 These results are in line with a systematic review and meta-analysis using 3,431 colorectal patients, which revealed a significant relationship between the increased CAR values and poor patient prognosis. 4 This study also concluded that a high CAR value indicates a poorer prognosis in colorectal cancer patients than a low CAR value, indicating that CAR is a valuable prognostic indicator to predict the radiologic response after NAC treatment.…”
Section: Discussionsupporting
confidence: 85%
“…A study conducted by Partl R et al, in 2020 concluded that the increased pretherapy CRP has a poor outcome in patients. 12 These results are in line with a systematic review and meta-analysis using 3,431 colorectal patients, which revealed a significant relationship between the increased CAR values and poor patient prognosis. 4 This study also concluded that a high CAR value indicates a poorer prognosis in colorectal cancer patients than a low CAR value, indicating that CAR is a valuable prognostic indicator to predict the radiologic response after NAC treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Similar to our results, an elevated CRP also predicted a bad prognosis. Particularly, in locally advanced rectal cancer patients, Parti et al [55] investigated the association of the pretreatment CRP plasma level with survival outcomes in a cohort of 423 consecutive patients treated with nCRT. In a multivariate analysis, the pretreatment CRP remained a significant prognostic factor for recurrence-free survival (HR = 1.013, 95%CI 1.001-1.025; p = 0.036), loco-regional control (HR = 1.014, 95% CI 1.001-1.027; p = 0.031), and metastasesfree survival (HR = 1.013, 95% CI 1.000-1.027; p = 0.046).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is accumulating evidence indicating that in ammation plays an important role in carcinogenesis and tumor proliferation [22]. There has been reported that in ammation-based markers could be used as a potential prognostic factor for many cancers, such as CRP, neutrophils, lymphocytes, dNLR, ALB [23][24][25]. Neutrophils secreted proangiogenic cytokines, including IL-8, MMP-9, MMP-8, and VEGF, and these cytokines contribute to tumor angiogenesis and progression [26,27].…”
Section: Discussionmentioning
confidence: 99%